A DISCUSSION OF THE RELATIONSHIP MODEL OF THE PURCHASE INTENTION OF BRANDS, AS BASED ON FOOD SAFETY ISSUES - Gu, Chao; Huang, Yonghang; Wei, Wei; Lin, Shuyuan (PEOPLE: International Journal of Social Sciences, 2020)
In recent years, food safety issues have been occurring in Taiwan, making food safety increasingly concerned and valued. Some people think that they should not buy the brands that have had food safety problems, while others think they can continue to buy the brands that have had food safety problems because the brands have made adjustments. For brands that have had food safety issues, the complex and diverse consumer attitudes are worth discussing. This study examines the relationship model of the subjects regarding brand image, food safety certification trust, brand trust, brand loyalty, and purchase intention of brands with food safety problems. The research methods used in this study include literature review, expert interview, and questionnaire survey, and data analysis methods include exploratory factor analysis, confirmatory factor analysis, and regression analysis. Finally, this study proposes the tested relationship model. The results of this study can provide a certain reference and theoretical basis for solving the food safety problems of brands.